Negative electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By forming a CNT layer without negative electrode active material on the negative electrode of the nonaqueous electrolyte secondary battery, the problem of large negative electrode mass is solved, and the weight reduction of the negative electrode and the improvement of the Coulomb efficiency are achieved.
Patent Information
- Application Number
- CN202380060857.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-01
AI Technical Summary
The negative electrode of the existing nonaqueous electrolyte secondary battery must contain negative electrode active substances, which leads to a large mass of the negative electrode and makes it difficult to achieve light weight.
A negative electrode active material layer without negative electrode active material is formed on the current collector, and a layer (CNT layer) composed of polyurethane resin and a single layer of carbon nanotubes is used to replace the traditional negative electrode active material layer.
By omitting the negative electrode active material, the quality of the negative electrode is reduced, and the Coulomb efficiency (charge and discharge efficiency) is improved, and the lightweight and efficient electrochemical performance of the nonaqueous electrolyte secondary battery is achieved.
Smart Images

Figure BDA0005278016860000191 
Figure BDA0005278016860000201 
Figure BDA0005278016860000211
Abstract
Description
Technical Field
[0001] Embodiments of the present invention relate to a negative electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery using the negative electrode. Background Art
[0002] Non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries are used as high-voltage, high-energy-density storage devices, for example, as a driving power source for electronic devices. The negative electrode of a non-aqueous electrolyte secondary battery is usually prepared by coating a mixture containing a negative electrode active material, a conductive auxiliary agent, and a binder on a current collector and drying the mixture to form a negative electrode active material layer, and the negative electrode active material is an essential component.
[0003] For example, Patent Document 1 describes that a mixed material electrode corresponding to a negative electrode active material layer formed on a current collector contains a negative electrode active material, carbon nanotubes as a conductive aid, and a binder such as polyvinylidene fluoride.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-153714 Summary of the invention
[0007] Technical problem that the invention aims to solve
[0008] In the past, as described above, negative electrode active materials were considered to be an indispensable component of the negative electrode of nonaqueous electrolyte secondary batteries. In contrast, if the negative electrode active material can be omitted from the negative electrode, the mass of the negative electrode can be reduced, thereby making the nonaqueous electrolyte secondary battery lighter.
[0009] An object of an embodiment of the present invention is to provide a negative electrode for a non-aqueous electrolyte secondary battery that can improve coulombic efficiency while omitting a negative electrode active material.
[0010] Technical solutions to the problem
[0011] The present invention includes the following embodiments.
[0012] [1] A negative electrode for a non-aqueous electrolyte secondary battery, comprising a current collector and a layer containing a polyurethane resin and single-walled carbon nanotubes disposed on the current collector, and containing no negative electrode active material.
[0013] [2] The negative electrode for a non-aqueous electrolyte secondary battery according to [1], wherein the polyurethane resin contains a lithium salt and / or a sodium salt of an anionic polyurethane resin.
[0014] [3] The negative electrode for a nonaqueous electrolyte secondary battery according to [1] or [2], wherein the polyurethane resin contains an alicyclic polyisocyanate as a raw material.
[0015] [4] The negative electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [3], wherein the mass ratio (A) / (B) of the polyurethane resin (A) to the single-walled carbon nanotubes (B) is 99.9 / 0.1 to 97.0 / 3.0.
[0016] [5] The negative electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [4], wherein the thickness of the layer containing the polyurethane resin and the single-walled carbon nanotube is 0.5 to 2 μm.
[0017] [6] A non-aqueous electrolyte secondary battery comprising the negative electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [5].
[0018] [7] The nonaqueous electrolyte secondary battery according to [6], wherein an ionic liquid is used as the electrolyte.
[0019] Effects of the Invention
[0020] According to the embodiment of the present invention, it is possible to provide a negative electrode for a non-aqueous electrolyte secondary battery that can improve coulombic efficiency (charge and discharge efficiency) while omitting a negative electrode active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of a nonaqueous electrolyte secondary battery according to one embodiment.
[0022] Figure 2 This is an exploded perspective view of an evaluation battery used in Examples. DETAILED DESCRIPTION
[0023] The negative electrode for a nonaqueous electrolyte secondary battery of the present embodiment includes: a current collector; and a layer (hereinafter sometimes referred to as “CNT layer”) disposed on the current collector and containing a polyurethane resin and single-walled carbon nanotubes.
[0024] [Current Collector]
[0025] The current collector is not particularly limited as long as it has electronic conductivity and can extract current to the outside. The current collector can be formed of, for example, metal materials such as copper, stainless steel, aluminum, nickel, titanium, conductive polymers, conductive glass, etc. In one embodiment, the current collector can be a metal layer formed of a metal material having electronic conductivity. As the metal layer, for example, it can be obtained by treating the surface of a metal layer such as copper with tin, nickel, titanium or silver, or it can be obtained by oxidizing the surface of the metal layer.
[0026] The shape of the current collector is not particularly limited. For example, the current collector may be a film such as a foil (foil) of a metal material, or may be a molded body such as a porous body or a foam body in addition to a sheet or plate. The current collector may also be a metal layer formed on a film or sheet made of a resin.
[0027] The thickness of the current collector is not particularly limited, and may be, for example, 1 to 1000 μm, 5 to 100 μm, or 10 to 50 μm.
[0028] [CNT layer]
[0029] The CNT layer is a layer containing a single-layer carbon nanotube as a conductive material and a polyurethane resin as a binder, and has conductivity. The CNT layer is a layer formed on the collector (i.e., the surface of the collector) instead of the previous negative electrode active material layer, and does not contain negative electrode active material. The CNT layer formed on the collector can be arranged on one side of the collector or on both sides.
[0030] A single-walled carbon nanotube is a carbon nanotube having a single-layer structure, which is a material having a shape in which a six-membered ring network (graphene sheet) composed of carbon is rolled into a cylindrical shape, and is also called a single-walled carbon nanotube (hereinafter, sometimes referred to as SWCNT).
[0031] The diameter (fiber diameter) of a single-walled carbon nanotube is not particularly limited, and the average diameter may be, for example, 0.4 to 100 nm, 0.5 to 10 nm, or 1.0 to 5.0 nm. The length of a single-walled carbon nanotube is not particularly limited, and the average length may be, for example, 50 nm to 1 mm, or 0.5 to 100 μm. The aspect ratio (i.e., the ratio of the average length to the average diameter) of a single-walled carbon nanotube is not particularly limited, and may be, for example, greater than 10, or greater than 100.
[0032] Here, the average diameter and average length of single-walled carbon nanotubes can be obtained by measuring the dimensions of 50 single-walled carbon nanotubes randomly selected from the atomic force microscope image and taking the arithmetic mean. For the mm-level length that cannot be measured by atomic force microscope, it can be measured using the image based on the microscope.
[0033] As the polyurethane resin, various water-based polyurethane resins such as anionic polyurethane resins, cationic polyurethane resins, and nonionic polyurethane resins can be used.
[0034] Anionic polyurethane resin is a water-based polyurethane resin having anionic groups and capable of being dispersed in water. Examples of anionic groups include carboxyl groups, sulfonic acid groups, phosphoric acid groups, and salts thereof. Any one of these anionic groups may be used or two or more may be combined. Examples of salts include alkali metal salts such as lithium salts, sodium salts, and potassium salts, and amine salts such as ammonium salts, primary amines, secondary amines, and tertiary amines.
[0035] Examples of the anionic polyurethane resin include resins obtained by reacting an active hydrogen-containing compound having two or more active hydrogen groups, an organic polyisocyanate, and a compound having an active hydrogen group and an anionic group. For example, an isocyanate group-containing urethane prepolymer is synthesized from an active hydrogen-containing compound having two or more active hydrogen groups, an organic polyisocyanate, and a compound having an active hydrogen group and an anionic group, and the urethane prepolymer is neutralized with a neutralizing agent, emulsified in water, and then chain extended with a polyamine compound to obtain an aqueous dispersion of the anionic polyurethane resin.
[0036] Here, the active hydrogen group refers to a group containing active hydrogen that reacts with an isocyanate group, and examples thereof include a hydroxyl group, a primary amino group (—NH 2 ), secondary amino group (-NHR).
[0037] The active hydrogen-containing compound having two or more active hydrogen groups refers to a compound having two or more active hydrogen groups in the molecule, and compounds known in the polyurethane industry can be used. For example, a compound having two or more hydroxyl groups and / or amino groups at the molecular end or in the molecule can be cited. Preferably, it is a polyol compound having two or more hydroxyl groups at the molecular end.
[0038] Specific examples of active hydrogen-containing compounds having two or more active hydrogen groups include ethylene glycol, propylene glycol, propane diol, butanediol, pentanediol, 3-methyl-1,5-pentanediol, hexanediol, neopentyl glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, dipropylene glycol, tripropylene glycol, 1,4-cyclohexanedimethanol, bisphenol A, bisphenol F, bisphenol S, hydrogenated bisphenol A, dibromobisphenol A, 1,4-cyclohexanedimethanol, dihydroxyethyl terephthalate, and hydroquinone. Polyol compounds or modified products thereof such as dihydroxyethyl ether, trimethylolpropane, glycerine, and pentaerythritol, alkylene oxide adducts thereof, or esters formed by the polyhydroxy alcohol or its alkylene oxide adduct and polycarboxylic acid, polycarboxylic acid anhydride or polycarboxylic acid ester, polycarbonate polyol, polycaprolactone polyol, polyester polyol, polyether polyol, polyacetal polyol, polytetramethylene glycol, polybutadiene polyol, castor oil polyol, soybean oil polyol, fluorine polyol, and silicone polyol. In addition, examples of alkylene oxides include ethylene oxide, propylene oxide, and butylene oxide.
[0039] Specific examples of the active hydrogen-containing compound having two or more active hydrogen groups include aliphatic polyamine compounds such as ethylenediamine, trimethylenediamine, propylenediamine, diethylenetriamine, and triethylenetetramine; aromatic polyamine compounds such as m-xylylenediamine, toluenediamine, and diaminodiphenylmethane; alicyclic polyamine compounds such as piperazine and isophoronediamine; and polyhydrazide compounds such as hydrazine and adipic acid dihydrazide.
[0040] The active hydrogen-containing compounds listed above may be used alone or in combination of two or more.
[0041] As the organic polyisocyanate, those known in the polyurethane industry can be used, and examples thereof include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates. Any one of these may be used, or two or more of them may be used in combination.
[0042] As aliphatic polyisocyanate, tetramethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate (HDI), 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate etc. are mentioned, for example.
[0043] As an alicyclic polyisocyanate, isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (hydrogenated MDI), hydrogenated xylylene diisocyanate, 1, 4- cyclohexane diisocyanate etc. are mentioned, for example.
[0044] Examples of the aromatic polyisocyanate include toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric MDI, xylylene diisocyanate (XDI), and naphthalene diisocyanate.
[0045] In addition, isocyanurate forms, adducts, biuret forms, allophanate forms, carbodiimide forms, etc. of these polyisocyanates may also be used. In addition, these organic polyisocyanates may be used alone or in combination of two or more.
[0046] As the compound having active hydrogen group and anionic group, for example, compounds having carboxyl group such as hydroxy acids such as glycol acid, malic acid, glycine, aminobenzoic acid, alanine, dimethylol propionic acid, dimethylol butyric acid, aminocarboxylic acid, polyhydroxy acids, compounds having sulfonic acid group such as aminoethyl sulfonic acid, 2-hydroxyethanesulfonic acid, hydroxysulfonic acids, etc. can be mentioned. Any one of them can be used, or two or more of them can be used in combination. In addition, as the neutralizing agent for neutralizing these anionic groups, for example, tertiary amine compounds such as alkali metal hydroxides such as lithium hydroxide, potassium hydroxide, sodium hydroxide, ammonia, trimethylamine, triethylamine, etc. can be mentioned, and any one of them can be used, or two or more of them can be used in combination.
[0047] Examples of the polyamine compound as the chain extender include the above-mentioned aliphatic polyamine compounds, aromatic polyamine compounds, alicyclic polyamine compounds, and polyhydrazide compounds.
[0048] The nonionic polyurethane resin is a non-charged aqueous polyurethane resin that does not have anionic groups and cationic groups and can be dispersed in water. Examples of the nonionic polyurethane resin include: a urethane prepolymer containing an isocyanate group synthesized from an active hydrogen-containing compound having two or more active hydrogen groups, an organic polyisocyanate, and an ethylene oxide adduct alone or an ethylene oxide and propylene oxide adduct of a monohydric alcohol or a polyhydric alcohol, and the urethane prepolymer is emulsified in water and then chain-extended with a polyamine compound.
[0049] The details and specific examples of the active hydrogen-containing compound having two or more active hydrogen groups, the organic polyisocyanate and the polyamine compound used in the synthesis of the nonionic polyurethane resin are as described above in the description of the anionic polyurethane resin.
[0050] The cationic polyurethane resin is a water-based polyurethane resin having a cationic group and capable of being dispersed in water. Examples of the cationic group include a quaternary ammonium group and the like.
[0051] Examples of the cationic polyurethane resin include resins obtained by reacting an active hydrogen-containing compound having two or more active hydrogen groups, an organic polyisocyanate, and a compound having an active hydrogen group and a cationic group. For example, an isocyanate-containing urethane prepolymer is synthesized from an active hydrogen-containing compound having two or more active hydrogen groups, an organic polyisocyanate, and a compound having an active hydrogen group and a cationic salt-forming group, a salt-forming agent is added to the prepolymer, and after emulsification in water, chain extension is performed using a polyamine compound, thereby obtaining an aqueous dispersion of a cationic aqueous urethane.
[0052] The details and specific examples of the active hydrogen-containing compound having two or more active hydrogen groups, the organic polyisocyanate and the polyamine compound used for synthesizing the cationic polyurethane resin are as described above in the description of the anionic polyurethane resin.
[0053] For compounds having an active hydrogen group and a cationic group, examples of compounds having an active hydrogen group and a salt-forming group include: N,N-dimethylethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine and other N-alkyldialkanolamines. Any one of these can be used, or two or more can be used in combination. In addition, as corresponding salt-forming agents, for example, organic acids such as formic acid, acetic acid, propionic acid, butyric acid, lactic acid, malic acid, malonic acid, adipic acid, dimethyl sulfate, diethyl sulfate, methyl chloride, benzyl chloride, etc.; inorganic acids such as formic acid, hydrochloric acid, phosphoric acid, nitric acid, etc.; compounds having reactive halogen atoms.
[0054] Among the various water-based polyurethane resins mentioned above, anionic polyurethane resins are preferably used from the viewpoint of dispersion stability of the negative electrode coating liquid composition formed by dispersing single-walled carbon nanotubes and polyurethane resin in water. In addition, from the viewpoint of being able to reduce the nucleation overvoltage (Japanese: nuclear formation overvoltage), as the polyurethane resin, alkali metal salts of anionic polyurethane resins are preferably used, and lithium salts and / or sodium salts of anionic polyurethane resins are more preferably used. In addition, from the viewpoint of being able to enhance the effect of improving the coulomb efficiency while reducing the nucleation overvoltage, lithium salts of anionic polyurethane resins are further preferably used.
[0055] In one embodiment, the polyurethane resin preferably contains a lithium salt and / or a sodium salt of an anionic polyurethane resin (i.e., at least one of a lithium salt and a sodium salt). More preferably, the polyurethane resin contains a lithium salt of an anionic polyurethane resin. In these cases, the amount of the lithium salt and / or the sodium salt of the anionic polyurethane resin (preferably the amount of the lithium salt of the anionic polyurethane resin) in 100% by mass of the polyurethane resin is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 100% by mass.
[0056] In one embodiment, the polyurethane resin preferably contains an alicyclic polyisocyanate as a raw material. That is, it is preferred to use an alicyclic polyisocyanate as the above-mentioned organic polyisocyanate, thereby being able to improve the dispersion stability of the negative electrode coating liquid composition. In this case, in 100% by mass of the organic polyisocyanate, the amount of the alicyclic polyisocyanate is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 100% by mass.
[0057] In one embodiment, as the polyurethane resin, lithium salts and / or sodium salts of anionic polyurethane resins containing alicyclic polyisocyanates as raw materials are preferably used. More preferably, lithium salts and / or sodium salts of anionic polyurethane resins obtained by reacting polyols containing polycarbonate polyols and / or polybutadiene polyols, organic polyisocyanates containing alicyclic polyisocyanates, and carboxyl-containing polyols are used. More preferably, lithium salts and / or sodium salts of anionic polyurethane resins obtained by chain extension of an isocyanate-containing urethane prepolymer obtained by reacting a polyol containing polycarbonate polyols and / or polybutadiene polyols, organic polyisocyanates containing alicyclic polyisocyanates, and carboxyl-containing polyols are used.
[0058] In the CNT layer, the mass ratio (A) / (B) of the polyurethane resin (A) to the single-walled carbon nanotube (B) is preferably 99.9 / 0.1 to 97.0 / 3.0, more preferably 99.7 / 0.3 to 97.5 / 2.5, and even more preferably 99.5 / 0.5 to 98.0 / 2.0.
[0059] The content of the polyurethane resin in the CNT layer is not particularly limited, but is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 97% by mass or more.
[0060] The CNT layer may be composed of only polyurethane resin and single-walled carbon nanotubes, but may also contain other components as long as the effect of the present embodiment is not impaired. As other components, for example, as a conductive material other than single-walled carbon nanotubes, multi-walled carbon nanotubes (MWCNT), acetylene black, ketjen black and other carbon blacks may be cited.
[0061] In addition, as other components, it may also contain: a binder other than the polyurethane resin, a dispersant for dispersing the single-walled carbon nanotubes in water, a thickener for adjusting the viscosity of the negative electrode coating liquid composition, etc. Specifically, it may include: polyvinylidene fluoride, styrene butadiene rubber, hydroxymethyl cellulose, carboxymethyl cellulose, and their alkali metal salts, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, polyacrylic acid, sodium polyacrylate, polyvinyl pyrrolidone, polyvinyl alcohol, sodium alginate, xanthan gum, carrageenan, guar gum, agar, starch, etc.
[0062] In one embodiment, the content of the dispersant such as carboxymethyl cellulose and / or its salt may be 10 to 300 parts by mass, 50 to 200 parts by mass, or 70 to 150 parts by mass relative to 100 parts by mass of the single-walled carbon nanotubes.
[0063] The thickness of the CNT layer is preferably 0.5 to 2 μm. That is, the thickness of the CNT layer may be less than 0.5 μm or more than 2 μm, but from the viewpoint of enhancing the processability of the CNT layer and the effect of the present embodiment, it is preferably 0.5 to 2 μm, and more preferably 0.7 to 1.5 μm.
[0064] [negative electrode]
[0065] The negative electrode of the nonaqueous electrolyte secondary battery of the embodiment can be produced by, for example, applying a negative electrode coating liquid composition prepared by dispersing single-walled carbon nanotubes and a polyurethane resin in water onto a current collector and evaporating water as a dispersion medium.
[0066] The negative electrode coating liquid composition contains single-walled carbon nanotubes, polyurethane resin and water as a dispersion medium, and may optionally contain the above-mentioned other components. The dispersion medium may be water alone, or may contain water and a polar organic solvent such as an alcohol or ketone solvent.
[0067] In this embodiment, the negative electrode of the nonaqueous electrolyte secondary battery does not contain a negative electrode active material. By not containing a negative electrode active material, the mass of the negative electrode can be reduced. In addition, by providing the above-mentioned CNT layer that does not contain a negative electrode active material, the mass of the negative electrode can be reduced and the coulombic efficiency can be improved.
[0068] The negative electrode active material is a material that can embed / de-embed metal lithium or lithium ions, and can be exemplified by materials commonly used as negative electrode active materials for non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries. Specific examples of negative electrode active materials include natural graphite, artificial graphite, difficult graphitized carbon, easy graphitized carbon, silicon oxide (SiO), silicon, silicon alloys, lithium titanate, and the like.
[0069] [Non-aqueous electrolyte secondary battery]
[0070] The non-aqueous electrolyte secondary battery of the present embodiment has the above-mentioned negative electrode. Here, the non-aqueous electrolyte secondary battery is a secondary battery using a non-aqueous electrolyte such as an organic solvent or an ionic liquid in the electrolyte, and in addition to the lithium ion secondary battery, it can also be cited as: sodium ion secondary battery, potassium ion secondary battery, calcium ion secondary battery, magnesium ion secondary battery, etc. Among them, the lithium ion secondary battery is preferred.
[0071] The nonaqueous electrolyte secondary battery comprises a negative electrode, a positive electrode and an electrolyte, and may also comprise a separator disposed between the positive electrode and the negative electrode. In the nonaqueous electrolyte secondary battery of the present embodiment, an electrode having a CNT layer containing a polyurethane resin and a single-layer carbon nanotube formed on the above-mentioned current collector and not containing a negative electrode active material is used as the negative electrode, and for structures other than the negative electrode, the structure of a known nonaqueous electrolyte secondary battery may be adopted.
[0072] Figure 1 Schematic diagram showing the structure of a nonaqueous electrolyte secondary battery 10 according to one embodiment. The nonaqueous electrolyte secondary battery 10 includes a negative electrode 12, a positive electrode 14, a separator 16 disposed between the negative electrode 12 and the positive electrode 14, and an electrolyte 18. The negative electrode 12 includes a negative electrode collector 20 and a CNT layer 22 disposed on the collector 20, and the negative electrode of the above embodiment can be used. The positive electrode 14 includes a positive electrode collector 24 and a positive electrode active material layer 26 containing a positive electrode active material disposed on the collector 24.
[0073] As the collector used in the positive electrode, the collector commonly used in lithium ion secondary batteries can be used, for example, foils containing metal materials such as aluminum, titanium, stainless steel, nickel, etc. can be cited. In addition, materials obtained by treating the surfaces of these metals such as carbon, nickel, titanium, silver, etc. can also be used.
[0074] The positive electrode active material layer is a layer containing a positive electrode active material, and may also contain a conductive aid and a binder while containing the positive electrode active material. As the positive electrode active material, the conductive aid and the binder, materials commonly used in lithium ion secondary batteries can be used, for example, the positive electrode active material can be listed as a composite oxide of lithium and transition metals such as lithium cobalt oxide, lithium manganate, lithium iron phosphate, and lithium nickel oxide.
[0075] As the separator, a separator generally used in lithium ion secondary batteries can be used, and examples thereof include porous resins made of polyethylene, polypropylene, polyolefin, polytetrafluoroethylene, etc., ceramics, nonwoven fabrics, and the like.
[0076] As an electrolyte, an electrolyte commonly used in lithium-ion secondary batteries can be used. Here, an electrolyte is a substance containing ions such as lithium ions that serve as charge carriers, and also contains a medium (solvent, etc.) that dissolves or disperses ionic crystals and is called an electrolyte. As an electrolyte, for example, non-aqueous electrolytes formed by dissolving ionic crystals such as lithium salts in organic solvents, non-aqueous electrolytes formed by dissolving ionic crystals such as lithium salts in ionic liquids, solid electrolytes, and gel electrolytes can be listed. Among them, from the perspective of obtaining a higher coulombic efficiency, it is preferred to use an ionic liquid for the electrolyte, for example, it is preferred to use an electrolyte formed by dissolving a lithium salt in an ionic liquid as an electrolyte.
[0077] Examples of lithium salts include LiPF 6 , LiBF 4 、LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiC(CF 3 SO 2 ) 3 、LiN(CF3 SO 2 ) 2 (i.e. LiTFSI), LiN(FSO 2 ) 2 (i.e. LiFSI), LiBC 4 O 8 Etc. Any one of these lithium salts may be used, or two or more of them may be used in combination. As the lithium salt, LiFSI and LiTFSI are preferred.
[0078] As an organic solvent for dissolving the lithium salt, for example, carbonates such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, ethylene glycol dimethyl carbonate, propylene glycol dimethyl carbonate, ethylene glycol diethyl carbonate, vinylene carbonate, lactones such as γ-butyrolactone, ethers such as dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,4-dioxane, sulfolanes such as sulfolanes, 3-methylsulfolane, dioxolanes such as 1,3-dioxolane, ketones such as 4-methyl-2-pentanone, nitriles such as acetonitrile, propionitrile, valeronitrile, benzonitrile, halogenated hydrocarbons such as 1,2-dichloroethane, etc. can be mentioned. Any one of them can be used, or two or more of them can be used in combination.
[0079] The ionic liquid that dissolves lithium salts is composed of cation components and anion components. It is liquid at room temperature (25°C), non-volatile, and has a high decomposition temperature. Examples of anion components contained in the ionic liquid include: BF 4 - PF 6 - , SbF 6 - 、NO 3 - CF 3 SO 3 - 、(FSO 2 ) 2 N - (i.e., FSI anion), (CF 3 SO 2 ) 2 N - (i.e. TFSI anion), (C 2 F 5 SO 2 ) 2 N - ,(CF 3 SO 2 ) 3 C - CF 3 CO 2 - , C3 F 7 CO 2 - , CH 3 CO 2 - 、(CN) 2 N - Etc. These may be used alone or in combination of two or more.
[0080] As the cationic component constituting the ionic liquid, for example, a compound containing elements such as N, P, S, O, C, and Si, a cation having a chain or a cyclic structure such as a 5-membered ring or a 6-membered ring as a skeleton can be cited. As the cyclic structure such as a 5-membered ring or a 6-membered ring, for example, heterocyclic structures such as a furan ring, a thiophene ring, a pyrrole ring, a pyridine ring, an oxazole ring, an isoxazole ring, a thiazole ring, an isothiazole ring, a furazan ring, an imidazole ring, a pyrazole ring, a pyrazine ring, a pyrimidine ring, a pyridazine ring, a pyrrolidine ring, a piperidine ring, a benzofuran ring, an isobenzofuran ring, an indole ring, an isoindole ring, an indolizine ring, and a carbazole ring can be cited. Among these cationic components, chain or cyclic compounds containing nitrogen elements are preferred, especially from the perspective of chemical and electrochemical stability. Examples of the nitrogen-containing cation include alkylammonium such as triethylammonium, 1-ethyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-methyl-1-propylpyrrolidinium, methylpropylpiperidinium, etc. Any one of these cations may be used, or two or more of them may be used in combination.
[0081] The concentration of the salt such as lithium salt in the electrolyte is not particularly limited, but is preferably 0.1 to 3.0 mol / L, and more preferably 0.5 to 2.0 mol / L.
[0082] The non-aqueous electrolyte secondary battery of the embodiment can be formed into a cylindrical, coin-shaped, square, or other arbitrary shapes. The basic structure of the battery is the same regardless of the shape, and can be implemented by design changes according to the purpose. For example, in a cylindrical type, the negative electrode and the positive electrode are wound into a winding body separated by a separator, and the winding body is stored in a battery can, and is obtained by injecting a non-aqueous electrolyte and sealing with insulating plates placed above and below. In addition, when applied to a coin-type battery, it is stored in a coin-type battery can in a state where a disc-shaped negative electrode, a separator, a disc-shaped positive electrode, and a stainless steel plate are stacked, and a non-aqueous electrolyte is injected and sealed.
[0083] Example
[0084] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited thereto.
[0085] The details of the current collector, conductive material, binder, and electrolyte used in the examples are as follows.
[0086] [Current Collector]
[0087] Cu foil: 15 μm thick copper foil (“NC-WS” manufactured by Furukawa Electric Co., Ltd.)
[0088] Cu—Sn foil: On the surface of a 15 μm-thick copper foil, a 0.5 μm-thick tin film is formed by the following film-forming method.
[0089] (Tin plating film forming method)
[0090] The Cu foil was immersed in a 0.1M hydrochloric acid aqueous solution for 1 second to remove the oxide on the surface of the Cu foil, then washed with pure water and dried. Then, the Cu foil was immersed in a Sn plating solution ("580M-Z series" manufactured by Ishihara Chemical Co., Ltd.) at 60°C for 5 minutes. Then, the Sn-plated copper foil was washed with pure water and punched out to produce a Cu-Sn foil.
[0091] [Conductive materials]
[0092] ·SWCNT: An aqueous dispersion having a single-walled carbon nanotube concentration of 0.99% by mass, prepared using single-walled carbon nanotubes ("TUBALL BATT" manufactured by OCSiAl, carbon purity >99%, average diameter = 1.6 nm, average fiber length = 5 μm) as a conductive material and using the following aqueous dispersion preparation method.
[0093] MWCNT: An aqueous dispersion having a multilayer carbon nanotube concentration of 0.99% by mass, prepared using multilayer carbon nanotubes (“Flotube 9110” manufactured by CNano, carbon purity >99%, average diameter = 12 nm, average fiber length = 10 μm) as a conductive material and using the following aqueous dispersion preparation method.
[0094] AB: An aqueous dispersion having an acetylene black concentration of 0.99% by mass, prepared by the following aqueous dispersion preparation method using acetylene black ("Li-400" manufactured by Denka Corporation) as a conductive material.
[0095] (Method for preparing aqueous dispersion)
[0096] 1.0 g of the conductive material was mixed with 100 g of a 1% aqueous solution of carboxymethyl cellulose salt ("Celogen 7A" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) in a beaker. After stirring, the slurry was dispersed for 90 minutes at an output of 100 μA while circulating the slurry using a beaker, an ultrasonic homogenizer ("US-600T" manufactured by Nippon Seiki Seisaku-sho, Ltd.), a circulation unit and a tube pump, thereby obtaining an aqueous dispersion of the conductive material.
[0097] [Adhesive]
[0098] WPU1: A water dispersion of a lithium salt of an anionic polyurethane resin obtained in Synthesis Example 1 below.
[0099] (Synthesis example 1)
[0100] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen blowing tube, 51.3 parts by mass of a polycarbonate polyol ("ETERNACOLL UH-100" manufactured by UBE Corporation, average hydroxyl value 110.0 mgKOH / g, number of active hydrogen groups 2.0), 5.1 parts by mass of dimethylolpropionic acid (number of active hydrogen groups 2), 2.6 parts by mass of trimethylolpropane (number of active hydrogen groups 2), 41.0 parts by mass of dicyclohexylmethane 4,4'-diisocyanate, and 150 parts by mass of methyl ethyl ketone were added, and reacted at 75° C. for 4 hours to obtain a methyl ethyl ketone solution of a urethane prepolymer having a free isocyanate group content of 3.0% by mass relative to nonvolatile components. The solution was cooled to 45° C., and a lithium hydroxide aqueous solution (1.59 parts by mass of lithium hydroxide monohydrate, 300 parts by mass of water) was slowly added, and emulsified and dispersed using a homogenizer. Next, an aqueous solution prepared by diluting 2.08 parts by mass of ethylenediamine (number of active hydrogen groups: 2) with 100 parts by mass of water was added to carry out a chain extension reaction for 1 hour. The solvent was removed under reduced pressure and heating at 50° C. to obtain a polyurethane resin aqueous dispersion having a nonvolatile content of about 32% by mass.
[0101] WPU2: A water dispersion of a sodium salt of an anionic polyurethane resin obtained in Synthesis Example 2 below.
[0102] (Synthesis example 2)
[0103] A polyurethane resin aqueous dispersion having a nonvolatile content of approximately 32% by mass was obtained in the same manner as in Synthesis Example 1 except that a sodium hydroxide aqueous solution (1.51 parts by mass of sodium hydroxide, 300 parts by mass of water) was used instead of the lithium hydroxide aqueous solution.
[0104] WPU3: A water dispersion of a lithium salt of an anionic polyurethane resin obtained in Synthesis Example 3 below.
[0105] (Synthesis example 3)
[0106] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen blowing tube, 74.1 parts by mass of polybutadiene polyol ("PolyVestHT" manufactured by Ebonic Corporation, average hydroxyl value 46.5 mgKOH / g, number of active hydrogen groups 2.32), 4.2 parts by mass of dimethylol propionic acid (number of active hydrogen groups 2), 21.7 parts by mass of dicyclohexylmethane 4,4'-diisocyanate, and 150 parts by mass of methyl ethyl ketone were added, and reacted at 75° C. for 4 hours to obtain a methyl ethyl ketone solution of a urethane prepolymer having a free isocyanate group content of 2.15% by mass relative to the non-volatile component. The solution was cooled to 45° C., and a lithium hydroxide aqueous solution (1.31 parts by mass of lithium hydroxide monohydrate, 300 parts by mass of water) was slowly added, and emulsified and dispersed using a homogenizer. Next, an aqueous solution prepared by diluting 1.05 parts by mass of diethylenetriamine (number of active hydrogen groups: 3) with 100 parts by mass of water was added to carry out a chain extension reaction for 1 hour. The solvent was removed under reduced pressure and heating at 50° C. to obtain a polyurethane aqueous dispersion having a nonvolatile content of about 32% by mass.
[0107] WPU4: A water dispersion of a triethylamine salt of an anionic polyurethane resin obtained in Synthesis Example 4 below.
[0108] (Synthesis Example 4)
[0109] In a four-necked flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen blowing tube, 51.3 parts by mass of polycarbonate polyol ("ETERNACOLL UH-100" manufactured by UBE Co., Ltd., average hydroxyl value 110.0 mgKOH / g, number of active hydrogen groups 2.0), 5.1 parts by mass of dimethylol propionic acid (number of active hydrogen groups 2), 2.6 parts by mass of trimethylol propane (number of active hydrogen groups 2), 41.0 parts by mass of dicyclohexylmethane 4,4'-diisocyanate, and 100 parts by mass of methyl ethyl ketone were added. Then, the mixture was reacted at 75°C for 4 hours to obtain a methyl ethyl ketone solution of a polyurethane prepolymer. The free isocyanate group content was 3.0% by mass relative to the nonvolatile component of the solution. The solution was cooled to 45°C, and after neutralization by adding 2.9 parts by mass of triethylamine, 300 parts by mass of water were slowly added, and emulsified and dispersed using a homogenizer. Next, an aqueous solution prepared by diluting 2.08 parts by mass of ethylenediamine (number of active hydrogen groups: 2) with 100 parts by mass of water was added to carry out a chain extension reaction for 1 hour. The solvent was removed under reduced pressure and heating at 50°C to obtain a polyurethane aqueous dispersion having a nonvolatile content of about 32% by mass.
[0110] SBR: Styrene-butadiene rubber (SBR) emulsion obtained in Synthesis Example 5 below.
[0111] (Synthesis Example 5)
[0112] In a flask equipped with a stirrer, a reflux condenser and a thermometer, 51 parts by mass of modulated water and 0.2 parts by mass of dodecylbenzene sulfonate were added and the temperature was raised to 40°C. In addition, the composition of the pre-emulsion was set to: 5 parts by mass of acrylonitrile, 8 parts by mass of methyl methacrylate, 55 parts by mass of styrene, 32 parts by mass of 1,3-butadiene, and 0.95 parts by mass of alkylbenzene sulfonate, which were emulsified and dispersed in 40 parts by mass of modulated water to prepare a pre-emulsion. The pre-emulsion was dripped into the above-mentioned flask with a dropping funnel for 4 hours, and 0.4 parts by mass of sodium persulfate initiator was added as a polymerization initiator in the form of a 10% by mass aqueous solution to start polymerization. After maintaining the reaction temperature of 65°C for 4 hours, the temperature was raised to 80°C, and the reaction was continued for 2 hours to obtain an SBR emulsion. Dilution water was added thereto to obtain an SBR emulsion with a non-volatile component of about 40% by mass.
[0113] [Electrolyte]
[0114] Electrolyte 1: LiFSI / MPPy-FSI (lithium salt: lithium bis(fluorosulfonyl)imide, ionic liquid: 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide), lithium salt concentration 1 mol / kg
[0115] Electrolyte 2: LiFSI / EC:DMC=1:1 (lithium salt: lithium bis(fluorosulfonyl)imide, organic solvent: ethylene carbonate / dimethyl carbonate=1 / 1 (volume ratio)), lithium salt concentration 1 mol / L
[0116] (Example 1 to Example 4, Comparative Example 1 to Comparative Example 4)
[0117] The conductive material and adhesive shown in Table 1 below were mixed in a manner to form the proportion shown in Table 1, and after the solid content concentration was adjusted to 12% by mass with water, a stirring treatment was performed for 10 minutes with a mixer. The adhesive / conductive material ratio in the table is the mass ratio of the resin solid content as the adhesive to the conductive material (the amount of single-layer carbon nanotubes, multi-layer carbon nanotubes or acetylene black as the conductive component). In addition, as a mixer, a vortex mixer ("VORTEX-GENIE 2Mixer" manufactured by Science Instruments) is used here, but it is basically independent of a stirring device. The obtained mixed solution is appropriately added dropwise to the collector attached to the glass substrate, and a spin coater ("MIKASA SPINNER" manufactured by Mikasa) is used to apply the mixture at a rotation speed of 2000rpm and a rotation time of 20 seconds. As a collector, Cu foil is used. The coated current collector was placed in a blower dryer and dried at 100° C. for 30 minutes to prepare a negative electrode.
[0118] The thickness of the coating film (layer containing a binder and a conductive material (CNT layer in the examples)) after drying was measured using a micrometer ("MDE-25PJ" manufactured by MITSUYO CORPORATION).
[0119] The coulombic efficiency was measured for the negative electrodes of Examples 1 to 4 and Comparative Examples 1 to 4. It should be noted that for Comparative Example 1, as a blank control, the current collector was used as a negative electrode without forming a coating film, and the coulombic efficiency (charge and discharge efficiency) was measured. The measurement method is as follows.
[0120] (Production of Evaluation Batteries)
[0121] The evaluation battery was constructed in a glove box under an argon atmosphere with a dew point below -70°C. Figure 2 As shown, a metal Li foil with a diameter of 13 mm is attached to the bottom surface of the first body of the bipolar battery for electrochemical measurement. A polyimide separator with a diameter of 20 mm is placed thereon, and the electrolyte 1 is impregnated under reduced pressure for 30 minutes. The above-mentioned negative electrode with a diameter of 14 mm is placed thereon, and the battery is sealed with the second body via an electrode pressing member and a spring to produce an evaluation battery.
[0122] (Measurement conditions of coulombic efficiency)
[0123] As a measuring device, a constant current charge and discharge device ("BTS2004W" manufactured by Nagano Co., Ltd.) was used to charge and discharge the above evaluation battery in a constant temperature room at 25°C. The current density was 1.00 mA / cm 2 , 1 mAh of Li is deposited on the negative electrode collector at a constant current. Then, a constant current discharge is performed until the cut-off voltage is 1.0 V for Li / Li + . This was repeated 50 times, and the average coulombic efficiency in the Li dissolution reaction was calculated. The average coulombic efficiency is the average value of each cycle of 100×discharge capacity / charge capacity (%). It should be noted that for evaluation batteries that cannot be charged or discharged and therefore do not operate as batteries, the coulombic efficiency is indicated as "not possible".
[0124] [Table 1]
[0125]
[0126] The results are shown in Table 1. Compared to Comparative Example 1, which is a blank control directly using copper foil as a current collector, if Examples 1 to 4 are examples in which a layer containing a polyurethane resin and a single-layer carbon nanotube is formed on the copper foil, the coulombic efficiency is still improved despite the absence of negative electrode active material. In contrast, compared to Comparative Example 1, which is a blank control, no improvement in coulombic efficiency was confirmed in Comparative Example 2, which uses styrene-butadiene rubber instead of polyurethane resin as a binder. In addition, in Comparative Examples 3 and 4, which use acetylene black or multi-layer carbon nanotubes instead of single-layer carbon nanotubes as conductive materials, charging and discharging are impossible and the battery cannot be operated.
[0127] For the salt form of the polyurethane resin as a binder, the sodium salt of Example 2 and the triethylamine salt (NEt 3 ) compared to Example 4, the effect of improving the coulombic efficiency in Example 1 as a lithium salt is excellent.
[0128] (Determination of nucleation overvoltage)
[0129] For the negative electrodes of Example 1, Example 2, and Example 4, the nucleation overvoltage was measured and evaluated as an index of resistance. In the measurement of the coulombic efficiency of the above-mentioned evaluation batteries using the negative electrodes of Example 1, Example 2, and Example 4, the difference between the minimum voltage at the time of initial charge and the voltage at the end of initial charge was defined as the nucleation overvoltage. The results are shown in the following Table 2.
[0130] [Table 2]
[0131] Example 1 Example 2 Example 4 Conductive material type SWCNT SWCNT SWCNT Adhesive Type WPU1 WPU2 WPU4 Salt type of adhesive Li Na <![CDATA[NEt 3 ]]> Coulomb efficiency (%) 97.9 97.7 97.7 Nucleation overvoltage (mV) 41 56 104
[0132] As shown in Table 2, as salt forms of polyurethane resin, lithium salt and sodium salt have lower nucleation overvoltage than amine salt, which is good. In addition, it is known that lithium salt is more advantageous than sodium salt in terms of reducing nucleation overvoltage and improving coulombic efficiency.
[0133] (Example 5 to Example 9, Comparative Example 5 to Comparative Example 6)
[0134] Cu-Sn foil was used instead of Cu foil as the current collector. In addition, the types and proportions of the binder and the conductive material were changed as shown in Table 3 below. The negative electrode was prepared in the same manner as in Examples 1 to 4 and Comparative Examples 1 to 4, and the coulomb efficiency was measured. For the negative electrodes with different coating thicknesses of Examples 6 and 7, the solid content concentration of the mixed solution was changed. It should be noted that, for Comparative Example 5, as a blank control, the Cu-Sn foil as the current collector was directly used as the negative electrode without forming a coating, and the coulomb efficiency was measured.
[0135] [Table 3]
[0136]
[0137] The results are shown in Table 3. Compared with the blank control, Comparative Example 5, which directly uses Cu-Sn foil as the current collector, when Examples 5 to 9 are formed with a layer containing polyurethane resin and single-layer carbon nanotubes on the Cu-Sn foil, the coulombic efficiency is improved despite the absence of negative electrode active material. Even if the thickness of the coating is changed,
[0138] The coulombic efficiency was also improved by changing the ratio of the binder to the conductive material. In contrast, in Comparative Example 6, in which styrene-butadiene rubber was used instead of polyurethane resin as the binder, the coulombic efficiency was lower than that of Comparative Example 5 as a blank control.
[0139] (Example 10, Comparative Example 7)
[0140] In Example 10, the coulombic efficiency was measured in the same manner as in Example 1, except that the electrolytic solution 2 using an organic solvent was used instead of the electrolytic solution 1 using an ionic liquid. For Comparative Example 7, as a blank control, the Cu foil as a current collector was directly used as a negative electrode without forming a coating film, and the coulombic efficiency was measured in the same manner as in Example 10, using the electrolytic solution 2 as the electrolytic solution.
[0141] [Table 4]
[0142]
[0143] The results are shown in Table 4. Even when the organic electrolyte 2 was used as the electrolyte, in Example 10 in which a layer containing a polyurethane resin and a single-walled carbon nanotube was formed on the Cu foil, the coulombic efficiency was improved compared to Comparative Example 7 as a blank control, although no negative electrode active material was contained.
[0144] It should be noted that, for various numerical ranges described in the specification, their upper limits and lower limits can be arbitrarily combined, and all of their combinations are described in this specification as preferred numerical ranges. In addition, the numerical range described as "X to Y" means more than X and less than Y.
[0145] Several embodiments of the present invention are described above, but these embodiments are given as examples only and are not intended to limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the invention. These embodiments and their omissions, substitutions, and changes are included in the scope and purpose of the invention, and are also included in the invention described in the claims and their equivalents.
[0146] Explanation of symbols
[0147] 10 Non-aqueous electrolyte secondary battery
[0148] 12 Negative electrode
[0149] 14 Positive electrode
[0150] 16 Diaphragm
[0151] 18 Electrolytes
[0152] 20 Current Collector
[0153] 22 CNT layers
[0154] 24 Current Collector
[0155] 26 Positive electrode active material layer
Claims
1. A negative electrode for a non-aqueous electrolyte secondary battery, characterized in that: The negative electrode for a non-aqueous electrolyte secondary battery comprises: a current collector; and a layer containing a polyurethane resin and a single-walled carbon nanotube disposed on the current collector, The negative electrode for a non-aqueous electrolyte secondary battery does not contain a negative electrode active material.
2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The polyurethane resin contains a lithium salt and / or a sodium salt of an anionic polyurethane resin.
3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The polyurethane resin contains an alicyclic polyisocyanate as a raw material.
4. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The mass ratio (A) / (B) of the polyurethane resin (A) to the single-walled carbon nanotube (B) is 99.9 / 0.1 to 97.0 / 3.
0.
5. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The layer containing the polyurethane resin and the single-walled carbon nanotube has a thickness of 0.5 to 2 μm.
6. A non-aqueous electrolyte secondary battery, characterized in that: A negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5.
7. The nonaqueous electrolyte secondary battery according to claim 6, wherein Ionic liquids are used in the electrolyte.
Citation Information
Patent Citations
Electrode for lithium ion secondary battery
JP2015153714A